2014
DOI: 10.1016/j.bbmt.2014.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Similar Transplantation Outcomes for Acute Myeloid Leukemia and Myelodysplastic Syndrome Patients with Haploidentical versus 10/10 Human Leukocyte Antigen–Matched Unrelated and Related Donors

Abstract: Allogeneic stem-cell transplantation for patients with acute myeloid leukemia (AML) and myelodysplastic syndromes (MDS) has been performed primarily with an HLA matched donor. Outcomes of haploidentical transplantation have recently improved, and a comparison between these donor sources in a uniform cohort of patients has not been performed. We evaluated outcomes of 227 patients with AML/MDS treated with melphalan-based conditioning. Donors were matched related (MRD) (N=87, 38%), matched unrelated (MUD) (N=108… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
185
7
9

Year Published

2015
2015
2019
2019

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 199 publications
(226 citation statements)
references
References 30 publications
25
185
7
9
Order By: Relevance
“…Furthermore, only 2 of 10 recipients who underwent HLAmatched sibling donor HSCT and 2 of 9 patients who received haploidentical or mismatched family donor transplants developed reactivation of CMV after receiving CAR T cells. These data compare favorably with our reported CMV reactivation rates of 41% following matched-sibling (44) and 71% following haploidentical HSCT (53), suggesting that CAR T cells may help with immune reconstitution. Furthermore, in contrast with the expected rate of 50% GVHD noted after traditional donor lymphocyte infusion (54), we observed a lower rate of acute GVHD (11%).…”
Section: Reinfusion Of Car T Cells and Antitumor Activity Independentsupporting
confidence: 86%
“…Furthermore, only 2 of 10 recipients who underwent HLAmatched sibling donor HSCT and 2 of 9 patients who received haploidentical or mismatched family donor transplants developed reactivation of CMV after receiving CAR T cells. These data compare favorably with our reported CMV reactivation rates of 41% following matched-sibling (44) and 71% following haploidentical HSCT (53), suggesting that CAR T cells may help with immune reconstitution. Furthermore, in contrast with the expected rate of 50% GVHD noted after traditional donor lymphocyte infusion (54), we observed a lower rate of acute GVHD (11%).…”
Section: Reinfusion Of Car T Cells and Antitumor Activity Independentsupporting
confidence: 86%
“…The others series reporting the results of PT-Cy Haplo-SCT in the specific fields of AML or MDS included few patients (18)(19)(20)(21)(22)(23)(24)(25), with various proportion of refractory diseases (36-100%). [25][26][27] They found a PFS ranging from 39 to 72%. More recently, Bacigalupo et al reported promising results in AML and MDS, especially when Haplo-SCT was performed in CR1.…”
Section: Discussionmentioning
confidence: 99%
“…MSD, MUDs and haploSCT cases had similar grade II-IV acute GVHD (24%, 19%, and 26%) for the ones in remission, whereas severe acute GVHD was reported to be of 4%, 4% and respectively 0%. PFS at 3 years was concluded to be similar (57%, 45%, and 41%) but a significant trend towards a better 3-year progression-free survival was reported in those with a matched sibling donor [22]. Thus, almost identical results are between haploSCT transplants and the matched ones, for both lymphoid and myeloid malignancies, mostly due to various conditioning chemotherapy regimens.…”
Section: Discussionmentioning
confidence: 79%